NATIONAL DANCES AND THEIR CULTURAL HERITAGE: THE SIGNIFICANCE OF UZBEK DANCES IN FOLK CULTURE, TRADITIONAL CUSTOMS AND THEIR EXPRESSION THROUGH DANCES - Khabibulla Akbarovich Saitov (Web of Journals Publishing, 2024)
The cultural heritage of Uzbek national dances forms an integral part of the people's historical, social, and spiritual values. This article examines the significance of Uzbek dances in folk culture, their connection to traditional traditions, and their role as a cultural heritage. Uzbek dances reflect such traditions as the people's way of life, respect for their spouses, wedding ceremonies, and the Navruz holiday. The article expresses opinions on the significance of dances in preserving national culture and their social role.
Keywords: Uzbek national dances, Cultural heritage, Folk culture, Traditional customs, Wedding dances, Navruz holiday, Dance and culture, social rituals, National identity.